BREEDING DURUM WINTER WHEAT FOR IMPROVEMENT OF ADAPTIVE POTENTIAL AND YIELD - G. V. Shchipak; R. A. Nedostupov; V. G. Shchipak (Вавиловский журнал генетики и селекции)
Major results and methods of many-year research in the creation of starting material for winter durum wheat breeding are presented. The new cultivars are assessed for grain yield, frost resistance and productivity elements.